ANALISIS TINGKAT KETERAMPILAN HIJAU PADA GURU DAN SISWA DI SEKOLAH MENENGAH KEJURUAN - Wahyuni, Nur; Mutohhari, Farid (Information Technology Education Department, 2024)
As climate change caused by human work continues to increase dramatically, one of the efforts that can be made is to encourage the growth of the green economy. Vocational high schools (SMK) are seen as one of the institutions that should play a role in the growth of green jobs and industries by equipping students with green job skills. Therefore, the first effort is to map the extent to which teachers and students have these skills, so the purpose of this study is to measure the level of generic green skills (KHG) in teachers and students which includes dimensions of cognitive, interpersonal and intrapersonal competencies. In addition, looking at the differences between dimensions as a whole was also carried out. The survey method was adopted with the help of KHG questionnaire instruments in SMKs that have Adiwiyata status. Data were analyzed using descriptive analysis, and ANOVA-Dunnet C Test. As a result, the KHG description of students still shows a low category, while teachers get a high category. However, teachers' KHG was not evenly distributed in each dimension. The interdimensional analysis did not show significant differences, both for teachers and students. These results indicate that there is still a need to strengthen teachers' pedagogy, especially in dimensions and indicators that are still weak. The last recommendation in improving KHG requires synergy from various fields, including society in general.